2017
DOI: 10.4172/2329-910x.1000244
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Complications after Primary Repair of Achilles Tendon Ruptures

Abstract: Background: Operative treatment of Achilles tendon ruptures is associated with lower rates of rereupture compared to nonoperative treatment. However, concerns regarding adverse events (AE) in the postoperative period such as wound complications and surgical site infection (SSI) persist. The purpose of this study was to identify patient characteristics associated with the occurrence of adverse events in Achilles tendon rupture (ATR) surgical repair cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Patients >40 years old and male patients did have lower scores. In a 30-day follow-up study of 615 patients by Pean et al (28), 2% had adverse outcomes. Smoking, obesity, and diabetes were not factors.…”
Section: Smokingmentioning
confidence: 96%
See 1 more Smart Citation
“…Patients >40 years old and male patients did have lower scores. In a 30-day follow-up study of 615 patients by Pean et al (28), 2% had adverse outcomes. Smoking, obesity, and diabetes were not factors.…”
Section: Smokingmentioning
confidence: 96%
“…Several additional studies found that obese patients displayed statistically significantly higher rates of wound complications, venous thromboembolism, and medical complications (23,24). In contrast, a smaller study did not find that obesity had any effect on the occurrence of adverse events after Achilles tendon repair (25).…”
Section: Obesitymentioning
confidence: 97%